Calommata (Atypidae) and new spider species (Araneae) from Israel - Levy, Gershom (Zootaxa, 2007)
The extraordinary finding in Israel of Calommata, a unique mygalomorph atypid, is reviewed. Another new find out of range concerns the cybaeid genus Paracedicus, represented in Israel by two new species: P. baram and P. geshur. Pitfall trapping yielded several new species disclosing among others populations inhabiting the sands of the southern Arava Valley of Oxyopes elifaz n. sp. or Cerbalus aravaensis n. sp. that resemble very closely psammophilous species living in the Haluza sands of the Negev. The unknown males of Ozyptila clavigera (O.P.-Cambridge, 1872), Tmarus hazevensis Levy, 1973, and Ebo eremus Levy, 1999 are described. In addition the following new species are described: Zoropsis thaleri, Zodarion geshur, Z. odem, Hahnia carmelita, Ozyptila sedotmikha, Xysticus sansan, Theridion zekharya, Singa ammophila and Neoscona lotan.